SOCIOECONOMIC DISPARITIES AND LATE ONSET GROUP B STREPTOCOCCUS IN TENNESSEE, 2010-2014 - Jones, Cassandra (My University, 2016)
My capstone project and field experience gave me the opportunity to increase my public health knowledge and skills. I spent the summer of 2016 at the Tennessee Emerging Infections Program at Vanderbilt University Medical Center in Nashville. Through my field experience, I learned how to obtain consent from patients for clinical trials, surveillance techniques, and how to extract pertinent health information from medical charts. I completed two projects during my time in Nashville. My minor project involved a random 10% audit of the 2015 Active Bacterial Core surveillance data and the creation of a database to house this and future audit information, and my primary project involved summarizing data on late onset group B Streptococcus and socioeconomic disparities in Tennessee from 2010-2015. Group B Streptococcus is the leading cause of neonatal sepsis. Since the introduction of the CDC’s Guidelines for the Prevention of Perinatal Group B Streptococcal Disease in 1996, the incidence rate of early onset disease has steadily declined. However, the incidence of late onset disease has remained stable. My primary project was to summarize late onset group B Streptococcus surveillance data for the preparation of a future, larger study. The purpose of this pilot was to identify areas of socioeconomic disparities for future analysis
Keywords: Bacterial Core surveillance; Tennessee; Group B Streptococcus